The Role of the Teacher in the Successful Implementation of the ADDIE Model in the Process of Islamic Learning in Diniyyah Formal - Ramdan, Muhammad; Tarsono; Mulyawan Safwandi Nugraha (Journal of Islamicate Studies, 2023)
The role of the teacher in implementing the ADDIE model in the learning process of Islamic Religion in formal diniyyah is crucial. The ADDIE model, as a learning framework, includes five important stages: Analysis, Design, Development, Implementation, and Evaluation. Teachers play a major role in each of these stages, from understanding students' needs and learning environment (Analysis), designing appropriate learning strategies (Design), developing relevant and quality materials (Development), to implementing classroom learning (Implementation), and evaluating its effectiveness (Evaluation). The role of the teacher is not only as a facilitator, but also as a designer who adapts the curriculum to meet the needs of students. With a deep understanding of students' characteristics and learning objectives, teachers can adjust teaching methods, materials and assessments to suit the ADDIE model. The teacher's ability to adapt and refine each stage of ADDIE is key to the successful implementation of Islamic learning in the formal diniyyah environment. In this context, improving teachers' skills in understanding, implementing and evaluating the ADDIE model effectively will support the success of the Islamic learning process. Continued support in training, resources and curriculum updates is needed so that teachers can continue to optimise their role in implementing the ADDIE model for the success of Islamic learning in formal diniyyah institutions.